MzmL, a novel marine derived N-acyl homoserine lactonase from Mesoflavibacter zeaxanthinifaciens that attenuates Pectobacterium carotovorum subsp. carotovorum virulence - Hao, Lingyun; Liang, Jinyou; Chen, Shuotian; Zhang, Junliang; Zhang, Yu; Xu, Ying (Frontiers in Microbiology, 2024)
Quorum sensing (QS) is a conserved cell-cell communication mechanism widely distributed in bacteria, and is oftentimes tightly correlated with pathogen virulence. Quorum quenching enzymes, which interfere with QS through degrading the QS signaling molecules, could attenuate virulence instead of killing the pathogens, and thus are less likely to induce drug resistance. Many Gram-negative bacteria produce N-acyl homoserine lactones (AHLs) for interspecies communication. In this study, we isolated and identified a bacterial strain, Mesoflavibacter zeaxanthinifaciens XY-85, from an Onchidium sp. collected from the intertidal zone of Dapeng Reserve in Shenzhen, China, and found it had strong AHL degradative activity. Whole genome sequencing and blast analysis revealed that XY-85 harbors an AHL lactonase (designated MzmL), which is predicted to have an N-terminal signal peptide and share the "HXHXDH" motif with known AHL lactonases belonging to the Metallo-βlactamase superfamily. Phylogenetic studies showed MzmL was closest to marine lactonase cluster members, MomL and Aii20J, instead of the AiiA type lactonases. Ultra performance liquid chromatography-mass spectrometry analysis confirmed that MzmL functions as an AHL lactonase catalyzing AHL degradation through lactone hydrolysis. MzmL could degrade both short-and long-chain AHLs with or without a substitution of oxo-group at the C-3 position, and retained full bioactivity under a wide range of temperatures (28-100 °C) and pHs (4-11). Furthermore, MzmL significantly reduced Pectobacterium carotovorum subsp. carotovorum virulence factor production in vitro, such as biofilm formation and plant cell wall degrading Deleted: including Pectobacterium carotovorum subsp.43 carotovorum (Pcc) that causes soft rot on a wide range of host 44 plants, produces 45 Deleted: s 46 Deleted: identified a marine invertebrate associated bacterial 47 strain, Mesoflavibacter zeaxanthinifaciens XY-85, with… 48 Deleted: s 49 Deleted: Pcc enzyme production, and inhibited soft rot development on potato slices. These results demonstrated that MzmL may be a novel type of AHL lactonase with good environmental stability, and has great potential to be developed into a novel biological control agent for bacterial disease management.